The New Frontier of Esports and Gaming: A Scoping Meta-Review of Health Impacts and Research Agenda - Kelly, Sarah; Leung, Janni (Frontiers in Sports and Active Living, 2021)
Given the rapid evolution of the gaming industry and the rising popularity of a hyper-connected, competitive esports version of online gaming, a meta-review of the impact of online competitive gaming upon health is timely. A scoping meta-review was conducted on 10 reviews that reported on any health consequences (physical, lifestyle, cognitive, mental, or social) of esports, online competitive gaming, or video gaming participation, as a player or spectator. While past reviews have examined health effects of video gaming, few have focused upon the newly evolved gaming context, incorporating both playing and streamed viewing, recognition as a professional sport, and potential career and exponential participation. Most past reviews have focused upon physical health impacts of video gaming among adolescents and young adults, but none have examined impacts of different forms of gaming participation in the new gaming era, and their potential differential health impacts. A scoping meta-review was undertaken on the physical, social, and psychological health outcomes of competitive online gaming and associated screen use, revealing a need for further review and research into lifestyle health outcomes including diet and sedentary behavior among young esports and competitive video gaming participants.